Seismicity at the Northern Hikurangi Margin, New Zealand, and Investigation of the Potential Spatial and Temporal Relationships With a Shallow Slow Slip Event. Issue 5 (13th May 2019) - Yarce, J.; Sheehan, A. F.; Nakai, J. S.; Schwartz, S. Y.; Mochizuki, K.; Savage, M. K.; Wallace, L. M.; Henrys, S. A.; Webb, S. C.; Ito, Y.; Abercrombie, R. E.; Fry, B.; et al.
Abstract: In 2014–2015, the Hikurangi Ocean Bottom Investigation of Tremor and Slow Slip experiment deployed seafloor absolute pressure gauges and ocean bottom seismometers directly above a large slow slip event, allowing examination of the relationship between slow slip and earthquakes in detail. Hikurangi Ocean Bottom Investigation of Tremor and Slow Slip data were combined with nearby existing land stations to create a catalog of microseismicity consisting of 2, 300 earthquakes ranging in magnitude between 0.5 and 4.7 that is complete to magnitude 1.5, yielding almost twice as many events as detected by the onshore networks alone. This greatly improves the seismicity catalog for this active subduction zone margin, especially in the offshore portion that was difficult to study using only the inland permanent seismic network. The new locations for the events within the footprint of the offshore network show that earthquakes near the trench are systematically shallower than and NW (landward) of their locations using only land‐based stations. Our results indicate that Hikurangi seismicity is concentrated in two NE‐SW bands, one offshore beneath the outer forearc wedge, one onshore beneath the eastern Raukumara Peninsula, and the majority of earthquakes are within the subducting Pacific plate with a smaller percent at the plate interface. We find a 20‐km wide northeast trending gap in microseismicity between the two bands and beneath the inner forearc wedge and this gap in seismicity borders the downdip edge of a slow slip patch. Key Points: 2, 313 earthquakes located in the Hikurangi margin, using ocean bottom seismometers and absolute pressure gauges from a temporary experiment Abundant earthquakes in the subducting Pacific plate suggest bending stress‐related fractures allowing upward migration of fluids Microseismic gap identified at down‐dip limit of the September‐October 2014 slow slip event coincides with interseismic coupling